Efektifitas Suhu Dan Lama Penyimpanan Pada Preparasi Sampel Darah Terhadap Volume Serum Pada Pemeriksaan Kadar Glukosa Puasa, Kolesterol Total Dan Trigliserida - Fitri Fadhilah; Ani Riyani; Anggi Nopiani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
This research is aimed to determine whether any differences between the volume of serum and the result of fasting glucose level test, total cholesterol, and triglycerides on the serum achieved by temperature variation and storage duration. This is an experimental research that has been done on October 2012 at Clinical Laboratory. From the research, there are average storage amounts of serum volume for 10 until 30 minutes on 80C raised to 93,4%, on 250C from the storage in 10 until 30 minutes raised to 138,8%, and on 370C from the storage 10 until 30 minutes raised to 30%. Based on statistical calculations derived Sig. (2-tailed) of <1.000, for the Sig. > 0.05 showed no significant correlation to storage time 10 minutes, 20 minutes and 30 minutes. ANOVA’s test result indicated that grade F achieved is less from grade F critical, that means there are no differences or meaningful effects from temperature and storage duration treatments to the result of fasting glucose level test, total cholesterol, and triglycerides . There is the increasing of serum volume after the temperature treatment is given and the storage duration on blood samples preparation. Moreover, there are no significant differences for the result of fasting glucose test, total cholesterol, and triglycerides.